2011
DOI: 10.1186/1752-1947-5-303
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced Elizabethkingia meningoseptica endophthalmitis: a case report

Abstract: IntroductionEndophthalmitis is a sight-threatening condition defined as any inflammation of the internal ocular spaces. It is classified as either endogenous or exogenous depending on the route of infection. Exogenous endophthalmitis results from direct inoculation as a complication of intra-ocular surgery, penetrating ocular trauma, intra-ocular foreign bodies, corneal ulceration and following a breach of ocular barriers from a periocular infection. We report a rare case of exogenous endophthalmitis with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Elizabethkingia meningoseptica , a Gram-negative ubiquitous bacillus, has been reported to be widely distributed in natural environments ( 1 , 2 ). It has also been reported to be associated with infections in humans leading to cerebrospinal meningitis in immunocompromised patients and neonates ( 3 , 4 ), endophthalmitis ( 5 ), and keratitis ( 6 ). Recently, draft genome sequences of E. meningoseptica 502 ( 7 ), NBRC 12535 T , and ATCC 13253 T ( 8 ) have been reported.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Elizabethkingia meningoseptica , a Gram-negative ubiquitous bacillus, has been reported to be widely distributed in natural environments ( 1 , 2 ). It has also been reported to be associated with infections in humans leading to cerebrospinal meningitis in immunocompromised patients and neonates ( 3 , 4 ), endophthalmitis ( 5 ), and keratitis ( 6 ). Recently, draft genome sequences of E. meningoseptica 502 ( 7 ), NBRC 12535 T , and ATCC 13253 T ( 8 ) have been reported.…”
Section: Genome Announcementmentioning
confidence: 99%
“…In the case described by Connell et al, self-infliction was suspected because of the unusual bacterial species involved and confirmed after subsequent patient questioning. 12 In the case of bilateral periocular metallic mercury injections, self-infliction was suspected after CT imaging and eventually confirmed by the patient. In another case, self-infliction was revealed only when prison guards witnessed the patient injecting drugs into his periocular tissues.…”
Section: Discussionmentioning
confidence: 91%
“…8 However, self-inflicted intraocular injections are very rare. A literature search of all articles in English revealed 5 previously documented cases of intraocular injection, 9-12 3 of which led to endophthalmitis, [11][12][13] and only 1 of which was bilateral (Table 1). 13 In our patient, self-inflicted endophthalmitis occurred from S. epidermidis in the right eye and S. viridans in the left eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Another case had keratitis that developed following trichiasis and exposure keratopathy. 13 Bloom et al 14 reported a case with keratitis caused by C. meningosepticum without ocular comorbidities.…”
Section: Discussionmentioning
confidence: 99%